Analysis of outbreak of tobacco caterpillar, Spodoptera litura (Fabricius) on soybean - S. RAMESH BABU; R. K. KALYAN; G. S. AMETA; MADAN LAL MEGHWAL (Journal of Agrometeorology, 2015)
An investigation was carried out to study the effect of various weather parameters on the occurrence of larva and adult population of Spodoptera litura and their factors for outbreak of this pest in soybean in Banswara, Rajasthan. The moth populations of S. litura were active from August to mid- October and decreased sharply in late October. The peak appearance was observed during September- October months and corresponded with peak activity of egg masses and larval population in soybean contributed to the outbreak of this pest during the reproductive stage of the crop. Overall correlation studies confirmed that the fluctuations in the male moth catches of S. litura per pheromone trap is mainly due to weather factors like, maximum temperature, rainfall, sunshine and wind speed. Moth population in pheromone traps will be used as a warning situation indicating the occurrence of larvae in the host for potential attack and to initiate timely management of S. litura in soybean.